PENGARUH KEPEMILIKAN SAHAM ASING, OPINI AUDIT, DAN PENGUNGKAPAN SUKARELA TERHADAP NILAI PERUSAHAAN PADA SEKTOR LOGAM DAN MINERAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021-2023 - SUPARLAN SUPARLAN; MISBAHRUDDIN MISBAHRUDDIN; BAIQ NAILI AMALIA; FATHIAH RAHMAN (Universitas Mahasaraswati K. Mataram, 2024)
The purpose of this research is to determine the influence of Foreign Share Ownership, Audit Opinion, and Voluntary Disclosure on Company Value. Using quantitative methods with multiple linear regression analysis. This research took a sample of 11 Metals and Minerals subsector companies listed on the Indonesia Stock Exchange (BEI) from 2021 to 2023 using census techniques. The results of the analysis show that partial foreign share ownership and audit opinion have a significant effect on company value, indicating that both can increase company performance and investor confidence. Voluntary disclosure does not have a significant impact on company value. Furthermore, foreign share ownership, audit opinion and voluntary disclosure together have a significant effect on company value. These findings provide important insights for company management on how to improve ownership and audit strategies to maximize company value.